Cutaneous Melanoma - Pietkiewicz, Paweł (IntechOpen, 2020)
According to the American Cancer Society, skin cancer is the most common cancer of all cancer types. Although melanoma represents only about 1% of all skin cancers, this tumour is still responsible for most skin cancer deaths and its incidence is steadily on the rise.The first section of this book covers the topic of genetic and epigenetic regulation of the melanoma progression. The second section focuses on special melanoma scenarios: melanoma in pregnancy and subungual melanoma. The third section follows the emerging trend of implementing mathematic models in skin cancer diagnosis. I hope that this book, written by international experts, will be a useful resource for both clinicians and researchers in the field.